2023
DOI: 10.3390/rs15092321
|View full text |Cite
|
Sign up to set email alerts
|

Application of Deep Learning for Classification of Intertidal Eelgrass from Drone-Acquired Imagery

Abstract: Shallow estuarine habitats are globally undergoing rapid changes due to climate change and anthropogenic influences, resulting in spatiotemporal shifts in distribution and habitat extent. Yet, scientists and managers do not always have rapidly available data to track habitat changes in real-time. In this study, we apply a novel and a state-of-the-art image segmentation machine learning technique (DeepLab) to two years of high-resolution drone-based imagery of a marine flowering plant species (eelgrass, a tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…CNN and RNN architecture is a hot topic in the deep learning community and a number of studies have already demonstrated the potential of such methods. Tallam et al [69], for example, applied a deep learning CNN for the image segmentation and classification of UAS-derived imagery of intertidal seagrasses, while Csillik et al [70] used a simple CNN to map the complex agricultural environment of a citrus tree plantation from UAS-derived imagery. Other studies have shown that the combination of OBIA and CNN resulted in less misclassification of fragmented coastal areas [71] and wetlands [38] than with SVM and RF or have shown the general benefits of using the OBIA framework for CNN applications [72][73][74].…”
Section: Future Recommendationsmentioning
confidence: 99%
“…CNN and RNN architecture is a hot topic in the deep learning community and a number of studies have already demonstrated the potential of such methods. Tallam et al [69], for example, applied a deep learning CNN for the image segmentation and classification of UAS-derived imagery of intertidal seagrasses, while Csillik et al [70] used a simple CNN to map the complex agricultural environment of a citrus tree plantation from UAS-derived imagery. Other studies have shown that the combination of OBIA and CNN resulted in less misclassification of fragmented coastal areas [71] and wetlands [38] than with SVM and RF or have shown the general benefits of using the OBIA framework for CNN applications [72][73][74].…”
Section: Future Recommendationsmentioning
confidence: 99%
“…In recent years, deep learning frameworks have shown great potential in the field of remote sensing applications, exhibiting impressive capabilities and performance [20][21][22][23][24][25][26]. There exist already some data-driven models based on optical images for sediment and habitat classification [27,28]. However, there is still very little research reported on datadriven approaches for classifying intertidal sediments and habitats using SAR images.…”
Section: Introductionmentioning
confidence: 99%
“…This relationship between the size of algal beds and their CO 2 absorption ability shows the importance of accurate area measurements in evaluating their role in blue carbon strategies [9]. Several studies have demonstrated the feasibility of identifying algal beds by analyzing aerial or unmanned aerial vehicle images, even though their primary focus has been on the detection of seaweed presence rather than blue carbon assessment [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…IoU = P overlap P pred + P gt − P overlap , (11) where P overlap represents the number of overlapping pixels between the predicted algal bed area and ground truth. • Precision: A metric that indicates the proportion of correctly predicted algal bed areas.…”
mentioning
confidence: 99%